Optionality at the syntax-discourse interface in near-native L2 speakers - SORACE, Antonella (SECOND LANGUAGE, 2007)
Recent second language (L2) research on the most advanced ('near-native') endstate of L2 acquisition marks a radical departure from previous L2 acquisition studies. While earlier research was almost exclusively concerned with the nature of L2 grammatical representations: much attention is now devoted to L2 speakers' processing abilities & how these interact with their grammatical knowledge at various stages of L2 development. Much of the impetus for this change has come from the discovery that there are striking convergences -- in terms of developmental stages, effects of one language system on the other, & determinacy of outcomes -- between L2 acquisition & other developmental domains such as first language (L1) attrition & bilingual L1 acquisition: one can observe similar patterns of optionality & variation in the same areas of grammar, namely at the interface(s) between "core" syntax & discourse pragmatics. As has been pointed out in experimental psycholinguistic research (e.g., Burkhardt, 2005), the investigation of syntax-discourse interface phenomena requires an understanding of the interplay of grammatical & extragrammatical factors &, in particular, a closer focus on the interaction among formal constraints on grammatical representations, discourse constraints on the contextual interpretation of language, & processing constraints on real-time language comprehension & production. The range of options available to the L2 speaker is grammatically based, but their actual selection in particular contexts is affected by processing principles; thus, a theory of language processing is needed to explain L2 development. This paper illustrates some issues arising from the study of interface phenomena by focusing on the development of the syntax-discourse interface in null subject languages, with a special emphasis on the interpretation & production of pronominal subjects. References. Adapted from the source document